Enhancing Junior High School Students’ Mathematical Problem-Solving Ability through GeoGebra-Assisted Project-Based Learning - Siska Aprilia; Novita Vindri Harini; Tatag Eko Yuli Siswono (Journal of the Indonesian Mathematics Education Society, 2026)
This study aimed to examine the effect of GeoGebra-assisted Project-Based Learning on students' mathematical problem-solving ability. This study is a quasi-experiment with a post-test only control group design. The population of this study was all eighth-grade students at SMP PGRI 2 Denpasar, distributed across 11 classes. The sample was determined using cluster random sampling to obtain 3 classes as the research sample. ANOVA results revealed a significant difference among the three learning models (F = 29.706, p < .05). Students taught through GeoGebra-assisted Project-Based Learning achieved significantly higher mathematical problem-solving scores than those taught through Project-Based Learning alone and the 5M model. Therefore, a further test was conducted using the Scheffe test. Based on the Scheffe test and the average scores of each sample group, it was found that the mathematical problem-solving ability of students who participated in project-based learning assisted by GeoGebra was better than that of students who participated in project-based learning alone and students who participated in the 5M model. Furthermore, it was found that the mathematical problem-solving ability of students who participated in project-based learning was better than that of students who participated in the 5M model. Therefore, it can be concluded that the GeoGebra-assisted project-based learning model is better than the project-based learning model alone and the 5M learning model in improving students' mathematical problem-solving ability.